Oral polio vaccine response in the MAL-ED birth cohort study: Considerations for polio eradication strategies. Issue 2 (7th January 2019) - Pan, William K.; Seidman, Jessica C.; Ali, Asad; Hoest, Christel; Mason, Carl; Mondal, Dinesh; Knobler, Stacey L.; Bessong, Pascal; ,
Abstract: Background: Immunization programs have leveraged decades of research to maximize oral polio vaccine (OPV) response. Moving toward global poliovirus eradication, the WHO recommended phased OPV-to-IPV replacement on schedules in 2012. Using the MAL-ED prospective birth cohort data, we evaluated the influence of early life exposures impacting OPV immunization by measuring OPV response for serotypes 1 and 3. Methods: Polio neutralizing antibody assays were conducted at 7 and 15 months of age for serotypes 1 and 3. Analyses were conducted on children receiving ≥3 OPV doses (n = 1449). History of vaccination, feeding patterns, physical growth, home environment, diarrhea, enteropathogen detection, and gut inflammation were examined as risk factors for non-response [Log2 (titer) < 3] and Log2 (titer) by serotype using multivariate regression. Findings: Serotype 1 seroconversion was significantly higher than serotype 3 (96.6% vs. 89.6%, 15 months). Model results indicate serotypes 1 and 3 failure was minimized following four and six OPV doses, respectively; however, enteropathogen detection and poor socioeconomic conditions attenuated response in both serotypes. At three months of age, bacterial detection in stool reduced serotype 1 and 3 Log2 titers by 0.34 (95% CI 0.14–0.54) and 0.53 (95% CI 0.29–0.77), respectively, and increased odds of serotype 3 failure by 3.0 (95% CI 1.6–5.8). Our socioeconomic index, consisting of Water, Assets, Maternal education, and Income (WAMI), was associated with a 0.79 (95% CI 0.15–1.43) and 1.23 (95% CI 0.34–2.12) higher serotype 1 and 3 Log2 titer, respectively, and a 0.04 (95% CI 0.002–0.40) lower odds of serotype 3 failure. Introduction of solids, transferrin receptor, and underweight were differentially associated with serotype response. Other factors, including diarrheal frequency and breastfeeding practices, were not associated with OPV response. Interpretation: Under real-world conditions, improved vaccination coverage and socio-environmental conditions, and reducing early life bacterial exposures are key to improving OPV response and should inform polio eradication strategies.